Allogeneic Hematopoietic Stem Cell Transplantation Despite Severe Fusarium solani Infection in a Lung Transplanted Patient—A Case Report - Monica Tozzi; Adele Santoni; Marta Franceschini; Margherita Malchiodi; Irene Bernareggi; Beatrice Esposito Vangone; Corrado Zuanelli Brambilla; Elisabetta Zappone; Mariapia Lenoci; Francesca Toraldo; Valeria Del Re; Alice Pietrini; et al. (Microorganisms)
Solid-organ transplant patients require prolonged immunosuppression, increasing their risk of hematologic disorders. For these conditions, allogeneic hematopoietic stem cell transplantation (HSCT) is a potential treatment, but it carries significant risk of treatment-related mortality due to the high possibility of developing rare infectious complications. We report a case of a 55-years-old male with a history of bilateral lung transplantation for extrinsic allergic alveolitis in 2015, who developed acute myeloid leukemia/myelodysplastic syndrome (AML/MDS) with TP53 mutation seven years later. During induction therapy, he experienced systemic fungal infection caused by Fusarium solani and he underwent HSCT conditioning with active intravitreal fungal infection. It is noteworthy that cases of patients undergoing HSCT after a prior lung transplant are exceedingly rare. The medical literature primarily documents cases where HSCT is performed first, followed by lung complications. Cases with the opposite timeline are extremely uncommon, and there is limited data on their outcomes; thus, the patient depicted here may help management and decision making of physicians facing this rare sequence of diseases and treatments.